Abnormality of m6A mRNA Methylation Is Involved in Alzheimer’s Disease - Han, Min; Liu, Zhen; Xu, Yingying; Liu, Xiangtian; Wang, Dewei; Li, Fan; Wang, Yun; Bi, Jianzhong (Frontiers in Neuroscience, 2020)
Alzheimer's disease (AD), the most common form of dementia, is highly prevalent in older adults. The main clinical feature is the progressive decline of memory function, which eventually leads to the decline of cognitive function. At present, the pathogenesis of AD is unclear. In the disease process, synaptic changes are the key. Recent studies have shown that dysregulation of RNA methylation is related to many biological processes, including neurodevelopment and neurodegenerative diseases. N6-methyladenosine (m6A) is the most abundant modification in eukaryotic RNA. In this study, RNA m6A methylation was quantified in APP/PS1 transgenic mice, which is an AD mouse model, and C57BL/6 control mice, and data showed that the m6A methylation was elevated in the cortex and hippocampus of APP/PS1 transgenic mice. Next, the alterations of m6A RNA methylation in AD and C57BL/6 mice were investigated using high-throughput sequencing. Genome-wide maps of m6A mRNA showed that the degrees of m6A methylation were higher in many genes and lower in others in AD mice. Interestingly, the expression of the m6A methyltransferase METTL3 was elevated and the m6A demethylase FTO was decreased in AD mice. The data was analyzed by Gene Ontology (GO) and KEGG pathway analyses, and pathways that might be related to synaptic or neuron development and growth were constructed. The related pathways and genes predicted the potential roles of the differentially expressed m6A methylation RNA in AD. Collectively, our findings demonstrate that the m6A methylation of RNA promotes the development of AD.